2014
DOI: 10.4028/www.scientific.net/msf.789.409
|View full text |Cite
|
Sign up to set email alerts
|

Hot Compression Deformation Behaviors and Microstructure Evolution for Brittle Au-20Sn Eutectic Alloy

Abstract: The hot compression test of Au-20Sn alloys with different solidification structures was carried out. The deformation behaviors and microstructure evolutions during hot compression were investigated. The results indicate that the fine fully lamellar eutectic structure without primary phase exhibited a very low yielding stress and a low stress platform, while the coarse lamellar with large primary Au5Sn phase showed rather high in that value. After compression, the lamellar eutectic tended to be equiaxed due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The hot compression deformation behaviors of Au-20Sn eutectic alloys with different solidification structures were investigated [8]. The results indicated that the fine fully lamellar eutectic structure without primary phase exhibited an excellent processing deformation performance.…”
Section: Resultsmentioning
confidence: 99%
“…The hot compression deformation behaviors of Au-20Sn eutectic alloys with different solidification structures were investigated [8]. The results indicated that the fine fully lamellar eutectic structure without primary phase exhibited an excellent processing deformation performance.…”
Section: Resultsmentioning
confidence: 99%